Entrepreneurship Education in Higher Education Welcomes Future Leaders in the Industrial Era 4.0 Towards Transition 5.0 - Jumadin, Jumadin; Nur, Hasanah; Makmur, Elfira (PINISI Discretion Review, 2024)
This research aims to explore the role of entrepreneurship education in higher education in facing the challenges of the Industry 4.0 era and the transition to Society 5.0. Using literature study methods, the study identified five key findings that focus on technology integration, sustainability in leadership, cross-disciplinary collaboration, digital transformation in learning, and partnerships with industry. The results show that many universities have not yet fully adopted technology-based skills, such as artificial intelligence and data analysis, in their entrepreneurship curriculum. However, universities that implement a cross-disciplinary approach and technology-based learning succeed in improving students' innovation and collaborative skills. In addition, the emphasis on sustainability-based leadership in the Society 5.0 era is considered important to create leaders who not only focus on profitability but also on social and environmental welfare. This research highlights the importance of partnerships with industry in strengthening the entrepreneurial ecosystem in higher education. These findings underscore the need for innovation in entrepreneurship education to prepare graduates who are ready to compete in the future.